Merajut Asa di Era VUCA : Tinjauan Literatur Mengenai Peran Pendidikan Kewirausahaan Digital - Mahendra Arya Wisnu Pradana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The VUCA era (volatility, uncertainty, complexity, ambiguity) requires education systems to equip young people with adaptive, creative, and resilient competencies. One strategic response to this challenge is digital entrepreneurship education. This study reviews academic literature from 2015 to 2025 to explore how digital entrepreneurship education contributes to addressing the dynamics of the VUCA era. Using a literature review approach, sources were gathered from the Scopus database and selected based on relevance. The analysis, conducted descriptively and qualitatively, identifies key findings. The results show that digital entrepreneurship education supports the development of student resilience and adaptability, offers practical experiences through digitalized and project-based learning, and fosters entrepreneurial intention. However, challenges remain, including limited integration of entrepreneurial values and digital ethics, unequal access to technology, educator readiness, and weak cross-sector collaboration. This review highlights the need for innovation in teaching approaches grounded in constructivist pedagogy, along with stronger synergy between education, industry, and technology. When guided strategically and inclusively, digital entrepreneurship education holds strong potential to prepare the next generation for an uncertain and fast-changing world.